Bugs A to Z - DeGezelle, Terri (Capstone Curriculum Publ, 2000)
Introduces the world of bugs through photographs and facts which describe one for each letter of the alphabet.
Keywords: Insects; Juvenile literature; Arthropoda; Juvenile literature; English language alphabet; Juvenile literature